NAVIGATING DIGITAL ECONOMY TRENDS: A THEORY OF PLANNED BEHAVIOR ANALYSIS OF GEN Z MUSLIM E-ENTREPRENEUR INTENTIONS - Abdul Hamid; Mohammad Arif; Hannani Hannani; Syaifullah Syaifullah; Damirah Damirah (Academic Bright Collaboration, 2026)
This study examines how Gen Z adult Muslims navigate digital economy trends by analyzing the influence of Islamic religiosity on e-entrepreneur intentions, with attitudes, perceived behavioral controls, and subjective norms as mediating variables based on Planned Behavior Theory (SDP). A quantitative cross-sectional survey was conducted with 387 Gen Z adult Muslim respondents recruited through purposive, convenience, and snowball sampling from selected Indonesian urban centers in Java and Sulawesi. Data were collected using a structured 5-point Likert scale questionnaire (22 items) and analyzed using PLS-SEM with SmartPLS 4.0. All seven hypotheses are supported. Islamic religiosity has a positive and significant direct effect on e-entrepreneurial intentions (t = 8.828, p < 0.001). Attitudes (t = 5.776, p < 0.001), perceived control of behavior (t = 4.803, p < 0.001), and subjective norms (t = 3.889, p < 0.01) also significantly predicted intention. Attitudes (indirect effects = 0.198), perceived control of behavior (0.163), and subjective norms (0.109) partially mediated the religiosity-intention relationship because the direct path from Islamic religiosity to intention remained significant. The model explains 48.3% of the variance in e-entrepreneurship intentions. These findings should be interpreted in the context of adult Muslim Gen Z respondents from specific Indonesian cities and should not be generalized to all Indonesian youth, rural populations, other religious groups, or developed country contexts. The cross-sectional design limits causal inference. Practically, universities, Islamic boarding schools, policymakers, and Islamic entrepreneurship institutions must integrate Islamic ethical values, digital skills, and community support into digital entrepreneurship programs. This study expands the SDGs by positioning Islamic religiosity as a religious-based cognitive antecedent of e-entrepreneurship intentions among Gen Z adult Muslims in Indonesia. It contributes to the theory of digital entrepreneurship in an Islamic context and offers evidence for value-based entrepreneurship education and policy design.